IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT BY ACTIVATING GROUP WORK - Nurtitah, Ayu Sastri Nurtitah; Afriani, Imroatul Husna Afriani; Rohmah, St. Shabibatul Rohmah (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2024)
This study was designed to improve students’ reading comprehension ofnarrative text by activating group works. This study is categorized as theClassroom Action Research (CAR) method in which to indetify and tosolve the problem on students’ reading comprehension. Reading is themost essential skill for the students’ success in learning English. However,there are still many problems faced by students in reading activities. Inthe Group Work Teaching Strategy activities, the students were trained tomake predictions, clarifications, questions, and summaries. In theimplementation of the strategies, students worked in small group. Thisstudy was conducted in one cycle with fifth meetings. There were 32students, consisted of 16 males and 16 females. The Grouping WorkTeaching Strategy that was implemented in teaching reading coveredfour strategies: predicting, clarifying, questioning, and summarizing. Thefinding showed that the students’ ability in reading comprehension hadimproved from individual to grouping. It could be seen that the students’involvement during the discussion in group improved 84%. Furthermore,in the reading test, the students were able to show their progress from52% to 85%. The result of this study will provide English teachers andalternative strategy.